2022
DOI: 10.1113/jp283605
|View full text |Cite
|
Sign up to set email alerts
|

Properties and modulation of excitatory inputs to the locus coeruleus

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…However, the vlPAG most certainly provides excitation to dorsal, ascending LC neurons as well. In line with this, a recent study of lateral PAG inputs to the LC reported excitatory postsynaptic responses in most LC neurons, without regard to subregion (33). It has been hypothesized that each module might be separately recruited via distinct synaptic inputs in the context of different behavioral states, which, at least in the context of pain modulation, would help reconcile their opposing pain facilitatory and pain inhibitory actions (18,19).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the vlPAG most certainly provides excitation to dorsal, ascending LC neurons as well. In line with this, a recent study of lateral PAG inputs to the LC reported excitatory postsynaptic responses in most LC neurons, without regard to subregion (33). It has been hypothesized that each module might be separately recruited via distinct synaptic inputs in the context of different behavioral states, which, at least in the context of pain modulation, would help reconcile their opposing pain facilitatory and pain inhibitory actions (18,19).…”
Section: Discussionmentioning
confidence: 92%
“…Unexpectedly, the synaptic features of these projections and their relevance to pain modulation have not been established. Although a rabies tracing study reported inputs to spinally projecting LC-NA neurons from vlPAG, and a slice electrophysiology study found an excitatory connection from lateral PAG to LC-NA neurons ( 31 33 ), previous in vivo electrophysiological recordings reported only weak, sparse input that predominantly inhibits LC discharge ( 34 ). Furthermore, vlPAG→LC neurons were reported to be inhibited by mu opioids ( 32 ), which conflicts with the notion that vlPAG output can drive descending LC neurons in the context of opioid analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, the antinociception produced by local morphine infusion into rat PAG partially depends on spinal NA ( 12 ). Furthermore, several PAG subregions, including the vlPAG, send excitatory projections to the LC and pericoerulear region ( 2932 ). Although optogenetic and chemogenetic activation of vlPAG glutamatergic neurons produces antinociception in mice ( 47 , 48 ), whether this is mediated by the LC, and whether vlPAG glutamatergic neurons support morphine antinociception, is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the synaptic features of these projections and their relevance to pain modulatory behavior have not been established. Although a rabies tracing study reported inputs to LC-NA neurons from vlPAG, and a slice electrophysiology study found an excitatory connection from lateral PAG to LC-NA neurons ( 3032 ), in vivo electrophysiological recordings reported only weak, sparse input that predominantly inhibits LC discharge ( 33 ). Furthermore, vlPAG-to-LC neurons were reported to be inhibited by mu opioids ( 31 ), which conflicts with the notion that vlPAG output can drive descending LC neurons in the context of opioid analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a putative central autonomic network [Benarroch, 1993], LC neurons can be driven by a number of factors that are either primarily cognitive (frontal cortex, thalamus) and/or primarily autonomic (brainstem, hypothalamus) [Jodo and Aston-Jones, 1997; Murphy et al, 2011Murphy et al, , 2014Joshi et al, 2016;deGee et al, 2017;Benarroch, 2018]. The LC receives inputs (Figure 1) from a limited set of cortical, cerebellar and subcortical regions including, but not limited to the amygdala, dorsolateral and medial prefrontal cortex possibly including subgenual and dorsal anterior cingulate cortex (dlPFC and mPFC, sgACC and dACC), the lateral hypothalamus (LH), periaqueductal gray and nucleus paragigantocellularis (PGi) [Price and Amaral, 1981;Veazey et al, 1982; Arnsten and Goldman- Rakic, 1984; Ennis and Aston -Jones, 1988;Pammer et al, 1990;Morecraft et al, 1992;Horvath et al, 1999;Chiba et al, 2001;Vogt et al, 2008;Schwarz et al, 2015; Breton-Provencher and Sur, 2019; Soya and Sakurai, 2020; Barcomb et al, 2022]. It must be stressed that there is very limited data showing the cortical inputs to LC in primates [Arnsten and Goldman-Rakic, 1984;Pammer et al, 1990;Chiba et al, 2001].…”
Section: B Inputs To the Locus Coeruleusmentioning
confidence: 99%